Budaya Global dalam Industri Budaya: Tinjauan Madzhab Frankfurt Terhadap Iklan, Pop Culture, dan Industri Hiburan - Arviani, Heidy (Global and Policy Journal of International Relations, 2013)
ABSTRACTNowadays, we live in the new global economy. Global brand represent a huge portion of our social identity and value. Consumer is the object of entertainment industry. Culture industry has taken over mainstream lifestyle. Global company using mass media (art, advertising, film, radio, television) as their main tool to spread consumptive lifestyle in all over the world. Through advertising and pop culture, consumer feel compelled to buy and use the products even though they see through mass media. Individually or socially, we are part of commercialism culture structure. Horkheimer and Adorno in their book „Dialectic of Enlightenment‟ develop culture industry concept. Frankfurt School point similarities between industrial and cultural production. Frankfurt School describe the blend between mass culture, advertising and consumption in consumer society. This paper will present media role in building culture structure and how Frankfurt school explain culture industry.Keywords: global culture, Frankfurt School, advertising, pop culture, entertainment industryDOI:https://doi.org/10.33005/jgp.v1i02.1993